Examining social support, self-efficacy, stress, and performance, in U.S. Division I collegiate student-athletes' academic and athletic lives. Issue 2 (4th May 2019) - van Raalte, Lisa J.; Posteher, Karlee A.
ABSTRACT: Stress can significantly harm ones physiological and psychological well-being. For student-athletes, the stress that accumulates across their dual roles as a student and an athlete is arguably unavoidable. The purpose of this study was to examine how social support is related to, if at all, the stress-coping process for collegiate student-athletes in their academic and athletic lives. This study included N = 459 Division I collegiate student-athletes from 18 different sports and institutions. Using a series of linear regressions, in both an academic and athletic setting, results revealed that stress negatively predicted self-efficacy; social support did not moderate the relationship between stress and self-efficacy; self-efficacy positively predicted performance; and self-efficacy partially mediated the relationship between stress and performance. It is suggested that institutional infrastructures consider targeting resources to emphasize all forms of social support to provide student-athletes with an overall sense of support.